Analysis of blood biomarkers and sports performance in crossfit athletes using the elevation training mask 2.0 post SARS-CoV-2 infection - David Jerves-Donoso; Manuel Garrosa; Juan Felipe Garcia-Sierra; Gema Santamaría; Jesús Seco-Calvo; Enrique Roche; Álvaro López-Llorente; Diego Fernández-Lázaro (Scientific Reports)
Abstract This study aimed to comparatively evaluate the hematological profile and sports performance in CrossFit® practitioners training using Elevation Training Mask (ETM) 2.0 after recovering from COVID-19 (1 month with no symptoms). Twenty trained male athletes were assigned to an experimental group (EG) (n = 10) using configured ETM and a control group (CG) (n = 10) using sham ETM device. Both groups completed 12 weeks of CrossFit® training after 1 month of finishing SARS-CoV-2 symptoms. Pre- and post-training testing included assessment of hematological biomarkers, and sports performance parameters in a single-blind randomized clinical trial (ID NCT06806124) following the Consolidated Standards of Reporting Trials. No significant differences (p > 0.05) were observed comparing EG and CG in the hematological profile and sports performance parameters evaluated. Significant differences (p < 0.05), group by time interaction effect, were observed throughout the 36 training sessions for CrossFit® Total and Fran WOD. Our findings could indicate improvements in both groups, CG and EG, in performance tests, without reaching pre-SARS-CoV-2 infection levels. Furthermore, ETM does not appear to function as an altitude simulator under the experimental conditions developed in the present intervention.